Reflexões sobre o desenho infantil sob o olhar da Pedagogia Waldorf - Cruz, Mariane Ribeiro da (Universidade Federal de São Carlos, 2015)
The present work addresses the following question-problem: what is Waldorf´s pedagogical proposal for children's drawing? In order to answer this main question, the research aimed to study the theoretical foundation of Waldorf pedagogy, understand the main stages of the development of drawing in early childhood, get to know the routine of Early Childhood Education at the Waldorf school, with a focus on development and the making of children's drawing. The research was carried out at the Waldorf Micael School located in the city of Sorocaba / SP, in a kindergarten class, with six children aged between one year and eight months to three and a half years. The work is organized in three chapters. Chapter I presents the theoretical framework, addressing Rudolf Steiner's biography, the basic principles of Anthroposophy, Waldorf Pedagogy and its Brazilian strand, the specificities of the Waldorf Kindergarten and the importance of children's drawing in the light of Waldorf Pedagogy. Chapter II describes the methodological paths and Chapter III presents the data analysis. The results indicate that the deep understanding of the human being adopted by the Waldorf pedagogy, which includes a conception of a child that respects his body, his limits and his will, allows the graphic records of each child to express movements and forces that are acting on him in a different way. free, lively and, above all, spontaneous.
Reflections on children's drawing from the perspective of Waldorf´s Pedagogy
Keywords: Desenho infantil; Children's drawing; Pedagogia Waldorf; Waldorf pedagogy; Primeira Infância; Early childhood; Corpo; Body; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO